United States : 2007 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that following an extended boom led by strong domestic demand, the slowdown in the United States has largely reflected a drag from residential investment as the housing market has weakened substantially. Unexpected weakness in business investment and net exports, as well as an inventory correction, amplified the downturn in early 2007, but growth is expected to recover in the remainder of the year. The most likely scenario is a soft landing of the U.S. economy, with growth picking up during 2007.